2021
DOI: 10.3389/fonc.2021.754541
|View full text |Cite
|
Sign up to set email alerts
|

NK Cells in the Tumor Microenvironment as New Potential Players Mediating Chemotherapy Effects in Metastatic Melanoma

Abstract: Until the last decade, chemotherapy was the standard treatment for metastatic cutaneous melanoma, even with poor results. The introduction of immune checkpoints inhibitors (ICIs) radically changed the outcome, increasing 5-year survival from 5% to 60%. However, there is still a large portion of unresponsive patients that would need further therapies. NK cells are skin-resident innate cytotoxic lymphocytes that recognize and kill virus-infected as well as cancer cells thanks to a balance between inhibitory and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 211 publications
0
16
0
Order By: Relevance
“…Because of their localization within tissues and their capability to promptly react to activating stimuli, ILCs may be involved in an early stage of an immune response to cancer cells. While the role played by NK cells in melanoma is firmly established (23,24), our knowledge about the potential role of other ILC subpopulations is limited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of their localization within tissues and their capability to promptly react to activating stimuli, ILCs may be involved in an early stage of an immune response to cancer cells. While the role played by NK cells in melanoma is firmly established (23,24), our knowledge about the potential role of other ILC subpopulations is limited.…”
Section: Discussionmentioning
confidence: 99%
“…In turn, this suggests that Nivolumab might improve the function of ILC2s and CD117 + ILCs not by directly affecting the interaction between melanoma cells and ILCs but rather by disrupting additional interactions mediated by PD-1 in vivo. Melanoma TME is enriched with suppressive immune cell subsets expressing PD-L1, such as macrophages, myeloid-derived suppressive cells (MDSCs) and regulatory T cells (Tregs) (24,45). ILC2s activity has been shown to be limited by suppressive subsets through cell-to-cell contact (46)(47)(48)(49), while similar data on CD117 + ILCs are missing.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, conventional chemotherapy has been described to directly induce death of malignant cells by intervening in cellular processes like DNA synthesis or replication. 35 However, increasing evidence suggests that the antitumor effects of several drugs can also rely on stimulation of the innate immune system by activating natural killer (NK) cells, 36 human complement, 37 or macrophages, 38 thus triggering an eradication of tumor cells. 39 Furthermore, combining cytotoxic drugs with antibodies can increase therapy effects compared with single treatments.…”
Section: Discussionmentioning
confidence: 99%
“…In this way, we can use FasL inhibitor to reduce its toxic effect on melanoma cells. Researchers have studied the principle of NK-exosomes killing melanoma cells ( 206 ), and tested the tumor-suppressive effect of NK-exosomes in vivo using a mouse model. It was found that the tumor size of the NK exosome-treated group was significantly smaller than that of the control group, indicating that NK cell exosomes induced the apoptosis of melanoma cells in vitro .…”
Section: Roles Of Exosomes In the Tmementioning
confidence: 99%